Reconstructing ancient linen body armor : unraveling the linothorax mystery - Aldrete, Gregory S. (Johns Hopkins University Press, 2013)
An extensive multiyear project in experimental archaeology, this study presents a thorough investigation of the linothorax, linen armor worn by the Greeks, Macedonians, and other ancient Mediterranean warriors. Because the linothorax was made of cloth, no examples of it have survived. As a result, even though there are dozens of references to the linothorax in ancient literature and nearly a thousand images of it in ancient art, this linen armor remains relatively ignored and misunderstood by scholars. Combining traditional textual and archaeological analysis with hands-on reconstruction and experimentation, the authors unravel the mysteries surrounding the linothorax.